Unravelling the structure of glycosyl cations via cold-ion infrared spectroscopy. Issue 1 (December 2018) - Mucha, Eike; Marianski, Mateusz; Xu, Fei-Fei; Thomas, Daniel; Meijer, Gerard; von Helden, Gert; Seeberger, Peter; Pagel, Kevin
Abstract Glycosyl cations are the key intermediates during the glycosylation reaction that covalently links building blocks during the synthetic assembly of carbohydrates. The exact structure of these ions remained elusive due to their transient and short-lived nature. Structural insights into the intermediate would improve our understanding of the reaction mechanism of glycosidic bond formation. Here, we report an in-depth structural analysis of glycosyl cations using a combination of cold-ion infrared spectroscopy and first-principles theory. Participating C2 protective groups form indeed a covalent bond with the anomeric carbon that leads to C1-bridged acetoxonium-type structures. The resulting bicyclic structure strongly distorts the ring, which leads to a unique conformation for each individual monosaccharide. This gain in mechanistic understanding fundamentally impacts glycosynthesis and will allow to tailor building blocks and reaction conditions in the future. Glycosyl cations are key intermediates in glycosylation reactions, but their structure has remained elusive due to their transient nature. Here, the authors perform an in-depth structural analysis and report that C2-participating protective groups induce acetoxonium cations with distinct ring conformations.